Understanding genome function: quantitative modeling of chromatin folding and chromatin-associated processes - Tark-Dame, Mariliis; Heermann, Dieter W. (Genome organization and function in the cell nucleus, 2011)
By way of its clear and logical structure, as well as abundant highresolution illustrations, this is a systematic survey of the players and pathways that control genome function in the mammalian cell nucleus. As such, this handbook and reference ties together recently gainedknowledge from a variety of scientific disciplines and approaches, dissecting all major genomic events: transcription, replication, repair, recombination and chromosome segregation. A special emphasis is put on transcriptional control, including genome-wide interactions andnon-coding RNAs, chromatin structure, ep
Keywords: Electronic books -- Electronic books